Pendekatan Indeks dalam Penilaian Keberlanjutan PAMSIMAS Pokmas Tambiliok Jaya di Desa Muara Jalai Kampar - Ardiansyah Hamid; Harmi Yelmi (PT Hakhara Akademia Indonesia, 2026)
The Community-Based Drinking Water and Sanitation Program (PAMSIMAS) is a community-based program aimed at increasing access to safe and sustainable drinking water in rural areas. Sustainability of the program is an important aspect to ensure that the facilities that have been built can continue to be used by the community in the long term. This study aims to analyze the sustainability index of the PAMSIMAS Program at the Tambiliok Jaya Community Group in Muara Jalai Village, North Kampar District, based on institutional, technical, financial, social, and environmental aspects. The study used a quantitative descriptive approach with data collection through distributing questionnaires using a Likert scale to respondents from the PAMSIMAS community. Data were analyzed using sustainability index methods, gap analysis, and ranking analysis. The results showed that the sustainability index value of the PAMSIMAS Program was 4.06, which is included in the high category. The institutional aspect obtained the highest value of 4.15, followed by the technical aspect at 4.11, the financial and environmental aspects each at 4.03, and the social aspect at 4.00. The gap analysis results showed that the institutional aspect had the smallest gap from the ideal condition, while the social aspect had the largest gap. The ranking analysis shows that the program's sustainability is supported by the integration of institutional, technical, financial, environmental, and social aspects, which are generally in the high category. Overall, the PAMSIMAS Program in Muara Jalai Village is sustainable and continues to optimally support the community's drinking water supply.